Description and Functional Benefits of Meeting Frequency, Intensity, and Time of Resistance and Cardiovascular Exercises: A Study of Older Adults in a Community-Based, Slow-Stream Rehabilitation, Hospital-to-Home Transition Program. (15th April 2022) - Maximos, Melody; Stratford, Paul; Tang, Ada; Dal Bello-Haas, Vanina
This prospective cohort study described cardiovascular and resistance exercises completed by older adults in a community-based, slow-stream rehabilitation, hospital-to-home transition program; compared exercises completed to the American College of Sports Medicine (ACSM) exercise guidelines; and, assessed differences in Late Life Function and Disability Index (LLFDI)-Function Component (FC) between older adults who met and did not meet the ACSM guidelines. Descriptive statistics and Factorial ANCOVA were conducted. For cardiovascular exercise 59.3% of participants met frequency, 73.4% met intensity, and 35.9% met time. For resistance exercise, 67.2% of participants met frequency, 42.2% met intensity, and 76.6% number of repetitions. Participants who met both frequency and time for cardiovascular exercise had higher LLFDI-FC scores, as did those who met intensity and/or number of repetitions for resistance exercise. The findings provide support that older adults engaged in a slow-stream rehabilitation program can meet the ACSM exercise guidelines for community-dwelling older adults, and that meeting the guidelines improves function.